Skin prick tests and subcutaneous immunotherapy with standardized allergens in children with moderate-to-severe allergic rhinitis - Nihar Ranjan Mishra; Karthik Nagaraju; Kasyapi Voorakaranam (Wolters Kluwer Medknow Publications, 2021)
Background: Allergic rhinitis is common in Indian children, one of the common triggers being house dust mites. Skin prick tests (SPTs) and subcutaneous immunotherapy (SCIT) using standardized extracts of these aeroallergens are increasingly being used in the diagnosis and the management of allergic rhinitis in India. Clinical Description: We describe three children with moderate-to-severe allergic rhinitis who were considered ideal candidates for SCIT based on persistent typical clinical symptoms causing significant functional impairment, despite multiple medications for years, and positive family history. Each displayed characteristic local signs (crease over nasal bridge, pale nasal mucosa, and hypertrophy of the inferior nasal turbinates) and normal systemic examination. Management: Each of the children displayed significant sensitization with allergens containing standardized preparations of Dermatophagoides pteronyssinus (Dp) and Dermatophagoides farinae (Df) on the basis of which it was decided to start them on SCIT using the standard protocol. Large local reactions developed and were managed conservatively. All three responded well to bi-weekly shots of progressively increasing concentrations used in the induction phase of SCIT, and are currently asymptomatic on monthly maintenance doses that will continue for 2-3 years. Conclusion: Pediatricians should consider referring children with moderate-to-severe allergic rhinitis to Pediatric Allergists for SCIT if significant wheals are observed on SPT. SCIT not only stops the progression of disease, and improve the quality of life, but is also known to prevent the development of bronchial asthma.